Adsorption of Pb(II), Zn(II) and Fe(II) Using Rubber Seed Shell - Siti Zaharah, Sulaiman (2012)
Adsorption of heavy metals by rubber seed shell, an alternative use of waste, chosen to investigate the their effectiveness of using rubber seed shell to remove heavy metal ions from aqueous solutions for the adsorbent’s economical feasibility and availability in large quantity. Rubber seed shell a waste and an inexpensive material, were investigated as an adsorbent for the removal of Pb(II), Zn(II) and Fe(II) ions from aqueous solutions using batch techniques. The purpose of this research is to investigate the potential of rubber seed shell as natural low cost adsorbent to adsorb Pb(II), Zn(II) and Fe(II) heavy metal ions by the variation of solution pH, contact time and initial concentration. The adsorbent was prepared by collecting the rubber seed shell, dried and ground it using grinder and mechanical sieve to specify the adsorbent to certain size. Adsorbate were prepared by diluting 100 mg/L of stock heavy metal solutions then used for testing the effect of removal of the heavy metal ions. 0.3g of rubber seed shell as adsorbent with 100 ml adsorbate was kept constant for this experiment where the adsorbate solution varied in pH= 2 to pH=10, using concentrated 0.1M NaOH and 0.1M HCl to change pH and put in a stackable incubator shaker, operated at 150rpm for 120minutes. For variation in contact time, the solution was set on the shaker for different sets of time from 40 minute until 120 minutes at constant 150rpm and 25˚C, with adsorbate concentration of 100mg/L. Initial adsorbate solution concentration of 100 mg/L was used with adsorbent sample varying in weight, 0.1g to 0.5g, set on shaker at constant 150 rpm and 25˚C. Adsorption isotherms were described by both Langmuir and Freundlich isotherms. Freundlich equation was found to represent the equilibrium data for adsorption of Pb(II), Zn(II), and Fe(II) using rubber seed shell (0.9391< R² <0.9857), and the maximum adsorption capacity was highest for Pb(II) with 14.41mg/g.Adsorption process using rubber seed shell was found to be suitable at pH2. Adsorption kinetic were conducted where both pseudo-first order and pseudo-second order yield values of R² from 0.7081 to 0.9768 and from 0.9982 to 1.0 for each order.